Cubic Splines with Least-Squares and Conditioned Curvature and Applications (Contemporary Mathematics, 2025)
In this article is detailed reviewed cubic splines with least-squares method and it is proposed a strategy for the interpolating spline obtained to have a conditioned curvature. The control of this curvature is done from a discrete point of view, resulting in an optimization problem. In the last part, some illustrative experiments and with practical applications have been exposed.
Keywords: least squares; cubic splines; discrete curvature; optimization